A Review of Friction Performance of Lubricants with Nano Additives - Muhammad Waqas (MDPI AG, 2021)
It has been established in literature that the addition of nanoparticles to lubricants at an optimum concentration results in a lower coefficient of friction compared to lubricants with no nanoparticle additives. This review paper shows a comparison of different lubricants based on the COF (coefficient of friction) with nanoadditives. The effect of the addition of nanoparticles on the friction coefficient was analyzed for both synthetic and biolubricants separately. The limitations associated with the use of nanoparticles are explained. The mechanisms responsible for a reduction in friction when nanoparticles are used as an additive are also discussed. Various nanoparticles that have been most widely used in recent years showed good performance within lubricants, including CuO (copper oxide), MoS2 (molybdenum disulfide), and TiO2 (titanium dioxide). The paper also indicates some research gaps that need to be addressed.